Technology Updates in Male Infertility Management - Aucky Hinting; Agustinus Agustinus (Indonesian Andrology and Biomedical Journal, 2021)
Background: Technologies are replacing manpower many fields including medical field. Several devices have been marketed for replacing/reducing manpower in the medical field including male infertility. Here we reviewed several technologies that developed in male infertility. Review: Computer assisted sperm analysis (CASA), Automatic assessment of biochemical marker of seminal plasma, B-mode ultrasound, and automatic sperm cryopreservation can be applied routinely. Several updates i.e. automatic histopathology assessment, ultrasound strain elastography, magnetic resonance imaging (MRI) stronger than 3.0 T, Artificial intelligence for predicting the presence of sperm in azoospermia cases, automatic sperm selection, and automatic intracytoplasmic sperm injection (ICSI) need more studies before their application. Summary: Prudent choice based on valid studies is needed in order to give a comprehensive management to patient with male infertility without using useless technology.